2017
DOI: 10.1590/1806-9061-2017-0470
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Selection Methods Using Body Weight on Egg Yield Parameters in Japanese Quail

Abstract: This experiment was conducted to investigate the effects of different selection methods of parent lines on the body weight of Japanese quails. For this purpose, line M 55 was subjected to individual selection for body weight at 5 weeks of age, while a reciprocal recurrent selection method was applied to lines R 33 and S 55 . Selection lasted two generations. Body weight changes, age and weight at sexual maturity, egg weight, and egg production were investigated in the parent generations as well as in the selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 18 publications
3
14
0
Order By: Relevance
“…Similarly improved body weight in Japanese quail was also observed in birds selected for higher body weight in many other studies as well (Baylan et al, 2009;Syed Hussein et al, 1995;Tozluca, 1993;Nestor et al, 1982). Anthony et al, (1996) observed that selected lines of Japanese quail produced heavier carcasses and more meat.…”
Section: Male Quail Birds' Performancesupporting
confidence: 65%
“…Similarly improved body weight in Japanese quail was also observed in birds selected for higher body weight in many other studies as well (Baylan et al, 2009;Syed Hussein et al, 1995;Tozluca, 1993;Nestor et al, 1982). Anthony et al, (1996) observed that selected lines of Japanese quail produced heavier carcasses and more meat.…”
Section: Male Quail Birds' Performancesupporting
confidence: 65%
“…Therefore, the selection for increased live body weight in earlier studies performed by Ryu et al [ 29 ] and Rehfeldt et al [ 30 ] was a suitable way to enhance Japanese quail’s growth performance. Baylan et al [ 31 ] reported a similar finding; Anjum et al [ 32 ] observed a higher breast meat yield in birds selected for body weight. In another explanation, Choi et al [ 33 ] reported a positive correlation between DNA contents and muscle weights between quail lines.…”
Section: Discussionmentioning
confidence: 68%
“…These reports were lower than our results. However, FCR was found by Kul et al (2006) 4.52–4.78, Baylan et al (2009) 3.89–4.36, and Şeker et al (2009) 4.15–5.07 in the same period. Thus, these reports were close to our results.…”
Section: Discussionmentioning
confidence: 74%
“…However, some researchers ( Aggrey et al , 2003 ; Adeogun and Adeoye 2004 ; Saatci et al , 2006 ; Aggrey 2009 ; Narinç et al , 2009 , 2013 ) reported lower values (91.63–168.12 g) than our study. By the way, Baylan et al (2009) determined considerable high BW at 5 weeks of age in quail range from 188.2 to 302.2 g. As shown in Table 1 , mean value of BW at 5 weeks of age in BHSS-2 was found significantly higher than means of other flocks ( P <0.01), 2.75% increase in BW trait occurred as a result of multi-trait selection. Baylan et al (2009) worked with three different lines and stated that there was a 3.32–9.12% increase in BW at 5 weeks of age with single trait selection.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation